Economic security and strategic sustainability of construction enterprises in conditions of cyclical fluctuations - Palahitskyi, V.; Kazmin, O.; Koshovy, B.; Shokotko, O.; Sysko, O. (Ways to Improve Construction Efficiency, 2023)
The article examines the issue of ensuring economic security and strategic sustainability of construction enterprises in conditions of cyclical fluctuations in the economy. The main factors influencing the activities of construction companies are analyzed, including macroeconomic instability, changes in state regulation, financial risks, fluctuations in the cost of resources, and technological challenges. Key threats to the economic security of enterprises are outlined, including a decline in investment activity, limited access to financing, instability in supply chains, increased competition, and the impact of global crises such as pandemics or military conflicts. The paper examines the essence of the concept of economic security of construction enterprises, the main factors of its formation and assessment. It is determined that the strategic stability of enterprises depends on their ability to predict crisis phenomena, adapt to changes in the market environment and effectively manage resources in conditions of instability, considers modern methods for assessing the level of economic security of construction enterprises, including financial indicators, market stability indicators, the level of digitalization and the effectiveness of management strategies. Particular attention is paid to the analysis of approaches to the formation of sustainable business models capable of ensuring adaptability to an unstable external environment. A set of measures has been proposed to enhance the strategic resilience of construction enterprises, including the diversification of financing sources, the implementation of innovative technologies, and the development of digital transformation. This includes the use of BIM technologies, automated management systems, and artificial intelligence for market risk forecasting and logistics process optimization. Additionally, the measures involve optimizing operational processes and strengthening crisis management through the creation of reserve funds, rapid response strategies to market changes, and the introduction of early warning systems for financial risks.